Joint Effect of Urinary Total Arsenic Level and VEGF-A Genetic Polymorphisms on the Recurrence of Renal Cell Carcinoma - Yang, Shu-Mei; Huang, Chao-Yuan; Shiue, Horng-Sheng; Huang, Shu-Pin; Pu, Yeong-Shiau; Chen, Wei-Jen; Lin, Ying-Chin; Hsueh, Yu-Mei (PloS one, 2015)
The results of our previous study suggested that high urinary total arsenic levels were associated with an increased risk of renal cell carcinoma (RCC). Germline genetic polymorphisms might also affect cancer risk and clinical outcomes. Vascular endothelial growth factor (VEGF) plays an important role in vasculogenesis and angiogenesis, but the combined effect of these factors on RCC remains unclear. In this study, we explored the association between the VEGF-A -2578C>A, -1498T>C, -1154G>A, -634G>C, and +936C>T gene polymorphisms and RCC. We also evaluated the combined effects of the VEGF-A haplotypes and urinary total arsenic levels on the prognosis of RCC. This case-control study was conducted with 191 RCC patients who were diagnosed with renal tumors on the basis of image-guided biopsy or surgical resections. An additional 376 age- and gender-matched controls were recruited. Concentrations of urinary arsenic species were determined by a high performance liquid chromatography-linked hydride generator and atomic absorption spectrometry. Genotyping was investigated using fluorescent-based TaqMan allelic discrimination. We observed no significant associations between VEGF-A haplotypes and RCC risk. However, the VEGF-A ACGG haplotype from VEGF-A -2578, -1498, -1154, and -634 was significantly associated with an increased recurrence of RCC (OR = 3.34, 95% CI = 1.03-10.91). Urinary total arsenic level was significantly associated with the risk of RCC in a dose-response manner, but it was not related to the recurrence of RCC. The combination of high urinary total arsenic level and VEGF-A risk haplotypes affected the OR of RCC recurrence in a dose-response manner. This is the first study to show that joint effect of high urinary total arsenic and VEGF-A risk haplotypes may influence the risk of RCC recurrence in humans who live in an area without obvious arsenic exposure.